Le « Tianxia » selon Zhao Tingyang - Jean-Paul Tchang (MONDE CHINOIS NOUVELLE ASIE, 2017)
This article presents the new book by Zhao Tingyang, professor at the Institute of Philosophy of the Chinese Academy of Social Sciences: "On the contemporaneity of Tianxia or the possibility of a world based on the Tianxia system", Citic Press, Beijing , 2016. The book defines the concept of Tianxia as a system of governance juxtaposing the Earth, the psychology of peoples and an inclusive global institution. Zhao Tingyang draws on the historical experience of the Zhou Dynasty (1046-256 BC). From the classical Chinese and foreign writings, it restores and analyzes the historical conditions of the advent and decline of the Tianxia system of the dynasty des Zhou, who in his conception of an inclusive world, was ahead of his time. Subsequently, the Tianxia inspired the Chinese political system, which Zhao describes as a veritable vortex formed by the game of conquering the constantly renewed central plain and which involved peoples and ethnic groups attracted by the natural and spiritual resources of this central plain. . Zhao opposes the Tianxia system erected as a political theory to the modern political theories of nation-states from the West. He proposes the Tianxia system as a new policy that would take the world and its sovereignty as subjects.